Impact assessment of seismic activity on fish catches using monitoring of fishery landings: a case study off Rio de Janeiro, Brazil - Holanda, Janaina Sales; Vasconcellos, Marcelo Cunha; da Silva, Alessandra Cristina (Arquivos de Ciências do Mar, 2014)
The seismic studies in Geophysics using air guns have been widely used in the oil and gas prospecting. This technology is classified as a main source of underwater noise, with still unknown effects on fisheries, particularly the artisanal fisheries. Reduction and increase in fishery production have been already observed, but these effects varying among species and used fishing gears. In Brazil, monitoring of fishing landings has being done as a condition of environmental licensing of seismic activity. Thus, the objective of the study was to identify effects of this activity on the fishing landings, including in the analysis covariates Sea Surface Temperature (SST) and Chlorophyll-a concentrations (Chla). Using Generalized Linear Models (GLM), the environmental variables and seismic activity were found to have low effect on landings productivity, direct and inverse trends were verified among catches and environmental variables, mainly for pelagic species. Current methodology of data collection showed serious flaws that have damaged the quality of the analysis, among which the lack of spatial information from catch locations and a fishing effort further detailed. Therefore a revaluation of the requirement of monitoring of fishing landings as a tool to identify the impacts of seismic activity on artisanal fishery is recommended.